PENGARUH KEADILAN PROSEDURAL, PENGHARGAAN, DAN DUKUNGAN SUPERVISOR KOMITMEN AFEKTIF KARYAWAN PT. WIJAYA KARYA (PERSERO) TBK SAMARINDA - HARI SAMPURNO; SUKISNO S. RIADI; SITI MARIA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this research was to verify the effect of procedural justice, organizational rewards, and supervisor support toward affective commitment of PT Wijaya Karya (persero) Tbk Samarinda employee. To collected the data this research, researcher used saturated sampling method. The sample which used  in this research was 60 respondents. This research used mulitple linear regression analysis with PLS as an instrument to calculate the data. The result showed that there was a positive effect and significant between procedural justice toward affective commitment. And there was a significant positive effect between organizational rewards toward affective commitment. And there was also a positive effect and significant between supervisor support  toward affective commitment.Keywords: Procedural  Justice, Organizational  Rewards, Supervisor Support, Affective Commitment.